Comparative analysis of the laws on termination of employment in the Republic of South Africa and the Republic of Ghana - Gyesi, Solomon (Department of Commercial Law, 2023)
This minor dissertation explores the standards set by the International Labour Organisation (ILO) on the reasons and procedure for termination of employment of employees as provided in ILO Convention 158. The reasons ILO approves as justifiable grounds for termination of contract employment include misconduct, incapacity and operational requirement. Though both Ghana and South Africa have not ratified the Termination of Employment Convention 1982, the former has developed elaborate labour legislations and case laws as vanguard for the protection of employment. Using a comparative approach, the dissertation examines the definition and court's interpretation of concepts of termination of employment and dismissals in Ghana and South Africa. The dissertation also compared the codified statutory procedures employers must follow prior to dismissal and came to the conclusion that Ghana lacks such precision and certainty in the substantive and procedural requirement for termination of employment. Though there are instances of similarities in Ghana and South African laws on termination of employment, there are several other areas Ghana can learn from South Africa. For this reason, the dissertation recommends amendments to the Labour Act of Ghana to include the safeguards identified in South Africa into Ghana's labour law.